A simple statistical approach to model the time-dependent response of polymers with reversible cross-links. (15th April 2017) - Brighenti, Roberto; Vernerey, Franck J.
Abstract: A new class of polymers characterized by dynamic cross-links is analyzed from a mechanical point of view. A thermodynamically consistent model is developed within the Lagrangian framework for polymers that can rearrange their internal cross-links. Such a class of polymers has the capability to reset their internal microstructure and the microscopic remodeling mechanism leads to a behavior similar to that of an elastic fluid. These materials can potentially be used in several fields, such as in biomechanics, smart materials, morphing materials to cite e few. However, a comprehensive understanding is necessary before we can predict their behavior and perform material design for advanced technologies. The proposed formulation –following a statistical approach adapted from classical rubber elasticity– is based on the evolution of the molecular chains' end-to-end distance distribution function. This distribution is allowed here to evolve with time, starting from an initial stress-free state and depending on the deformation history and the cross-link attachment/detachment kinetics. Some simple examples are finally presented and discussed to illustrate the capability and generality of the developed approach.